2015
DOI: 10.1097/pas.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous NK/T-cell Lymphoma, Nasal Type and CD56-positive Peripheral T-cell Lymphoma

Abstract: Primary cutaneous, extranodal natural killer/T-cell lymphoma, nasal type (PC-ENKTL), is a rare Epstein-Barr virus (EBV)-associated neoplasm with poorly defined clinicopathologic features. We performed a multinational retrospective study of PC-ENKTL and CD56-positive EBV-negative peripheral T-cell lymphoma (PC-CD56+PTCL) in Asia in an attempt to elucidate their clinicopathologic features. Using immunohistochemistry for T-cell receptors (TCRs), in situ hybridization for EBV, and TCR gene rearrangement, we classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 25 publications
3
66
0
Order By: Relevance
“…In the eight cases positive for TCR, the αβ T-cell and γδ T-cell tumors were equal in number. 7 In agreement with these data from Takata et al, 50% of the T-lineage ENKTLs lacked TCR in the present study. Absence of TCR expression might be a common phenomenon in T-cell lymphoma and was also reported in EATL.…”
Section: Modern Pathology (2016) 29 430-443supporting
confidence: 94%
See 4 more Smart Citations
“…In the eight cases positive for TCR, the αβ T-cell and γδ T-cell tumors were equal in number. 7 In agreement with these data from Takata et al, 50% of the T-lineage ENKTLs lacked TCR in the present study. Absence of TCR expression might be a common phenomenon in T-cell lymphoma and was also reported in EATL.…”
Section: Modern Pathology (2016) 29 430-443supporting
confidence: 94%
“…In cases of ENKTL, previous studies applying conventional PCR techniques showed wide ranges of T-cell clonality ranging from 0 to 71.4%, 5,6,18,19 while T-cell clonality ranged from 0 to 26% by BIOMED-2 multiplex PCR analysis. 7,8,10,20 The traditional PCR design with a few consensus primers to detect TCR gene rearrangement yields frequent falsenegative results because the primers cannot cover extensive sequence variations. On the other hand, a lack of further analysis of PCR products can produce false-positive results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations